An antibacterial mechanism of titanium alloy based on micro-area potential difference induced reactive oxygen species. (20th August 2022) - Fu, Shan; Zhang, Yuan; Yang, Yi; Liu, Xiaomeng; Zhang, Xinxin; Yang, Lei; Xu, Dake; Wang, Fuhui; Qin, Gaowu; Zhang, Erlin
Highlights: Micro-area potential difference (MAPD) existed on Ti-M alloy due to the second phase formation. MAPD played a key factor in the antibacterial properties of titanium alloys. MAPD enhances the galvanic reaction and electron transfer of Ti-M alloy. Electron transfer induces ROS in bacteria but does not affect MC3T3 proliferation and adhesion. Abstract: Antimicrobial material is highly desired because of the increasing demand in biomedical application to prevent from the formation of biofilm. A common strategy for enhancing the antibacterial property of a metal material is to incorporate toxic metal such as Cu and Ag. However, the reported Cu 2+ or Ag + released concentration from antibacterial alloys was much less than the reported minimum inhibitory ion concentrations (MIC), revealing the existence of an unknown alternative antimicrobial mechanism not relying on the toxicity of the metal ions. Herein, we proposed a new antibacterial mechanism that the antibacterial effectiveness of the different alloys is proportional to the micro-area potential differences (MAPDs) on the surface of the alloys. We designed three kinds of Ti-M (M=Zr, Ta and Au) alloys to eliminate the potential antibacterial contribution from Cu and Ag ion. We demonstrated that high MAPDs are associated with great production of reactive oxygen species (ROS), resulting in the killing effect to the biofilm known to be associated with implant infections ( Staphlococcus aureus and Escherichia coli ). These results provide new insights for the design of antibacterial alloys.